Internationalizing higher education: from grand plans to evolving responses. Issue 6 (3rd October 2016) - Mertkan, Sefika; Gilanlioglu, Ilkay; McGrath, Simon
Abstract : Purpose: The purpose of this paper is to explore the complexity of developing into an international institution from the perspective of higher education leaders through the case study of one institution engaged in institutional transformation. Design/methodology/approach: This study employs the qualitative approach and involves in-depth interviews with key institutional managers. Findings: Findings suggest internationalization is a dynamic change process that goes beyond the rational and predictive elements of internationalization and cannot be confined to the rational planning and grand plans solely at institutional level. Reciprocal influence of different levels of analysis – institution, society and the nation – needs to be acknowledged and internationalization efforts need to go beyond the confines of the institution and extend into the society and the nation as a whole. Originality/value: Internationalization of higher education has been widely examined, but the reciprocal influence of different levels of analysis on the internationalization efforts of higher education institutions is thin to which this paper contributes.